Early intervention and dementia care: innovation and impact. (4th March 2014) - Seabrooke, Viniti; Milne, Alisoun
Abstract : Purpose: – This study aims to systematically evaluate the impact and effectiveness of two early intervention services in NW Kent. Design/methodology/approach: – Data were gathered via evaluation questionnaires for both projects; these included quantitative post-intervention data and qualitative comments. Data on referrals to secondary care and a specialist third sector organisation were also collected for the primary care project. Findings: – Findings from the primary care project indicate that targeting a specific age cohort of patients can be effective in terms of: early identification of dementia-related concerns, the provision of support, appropriate referrals to secondary care, and increased referrals to a third sector dementia service. At the end of the project most practitioners felt they were better informed about dementia, more committed to facilitating early diagnosis, and had gained confidence in using a screening tool (the General Practitioner Assessment of Cognition Test). Evidence from evaluating the Carers Group suggests that attendance helped members manage emotional difficulties, increased understanding of dementia, and enhanced coping skills. They also felt less isolated and knew how to access support services. Practical implications: – The projects offer two models of intervention: how a proactive third sector agency can work with primary care professionals to enhance commitment to dementia case finding and the provision of group support to relatives of those in receipt of a recent dementia diagnosis. Originality/value: – The study provides insights into early intervention in dementia care how to evaluate impact of effectiveness.